Tecnologías de la información y la comunicación en el área de lengua y comunicación para el séptimo año de educación general básica, año 2014 - Arteaga Llerena, Lina Leonor (2015)
TIC Educational, are more important digital tools that contribute to the achievement of its aims, which allow developing the educational creative capacity of a class; using different technological resources and the implementation of an interactive CD in the area of Language and Communication for the seventh year of basic general education, It seeks to streamline processes and increase academic performance of students; the exposure of multimedia content, it is possible to apply and obtain favorable results, considering that do the context of an educational institution for find through innovative processes, a change in teaching practice, allowing students getting a scientific humanistic education.